Functional molecular analysis of a circadian clock gene timeless promoter from the Drosophilid fly Chymomyza costata - Kobelková, Alena; Bajgar, Adam; Dolezel, David (Journal of biological rhythms, 2010)
The circadian transcription of the tim gene is tightly regulated by the protein complex dCLK/CYC, which directly interacts with a series of closely spaced E-box and E-box-like elements in the Drosophila timeless promoter. The tim promoter from D. melanogaster has been studied in detail both in tissue cultures and in living flies yet has never been investigated in other species. This article presents a detailed functional analysis of the tim promoter from the drosophilid fly, Chymomyza costata, in Drosophila tissue cultures. A comparison of tim promoters from wt and npd-mutants confirmed that the 1855 bp deletion in the latter removes crucial regulatory cis-elements as well as the minimal promoter, being subsequently responsible for the lack of tim mRNA expression. Deletion and substitution mutations of the wt tim promoter showed that the region containing the canonical E-box, TER-box, and 2 incomplete E-box sequences is essential for CLK/CYC-mediated expression, while the PERR element appears to be a repressor in S2 cells. Furthermore, the expression of the circadian genes timeless, period , vrille, and doubletime was quantified in C. costata adults. Striking differences were found in expression profiles for tim, per, and vri between wild-type and npd-mutant individuals.
Keywords: Circadian Clocks; Drosophila melanogaster; Drosophila Proteins; druhová specificita; sekvence nukleotidů; Cell Line; Sequence Homology, Nucleic Acid; mutace; proteiny Drosophily; Drosophilidae; Transcription, Genetic; hmyzí proteiny; molekulární sekvence - údaje; sekvenční homologie nukleových kyselin; promotorové oblasti (genetika); elementy E-Box; Species Specificity; E-Box Elements; genetická transkripce; Animals; zvířata; Promoter Regions, Genetic; buněčné linie; Insect Proteins; Molecular Sequence Data; Base Sequence; Mutation; cirkadiánní hodiny